Tapping the Power of PowerPoint for Medical Posters and Presentations - Thakur, Anand J.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book talks about developing and improvising upon medical presentations by equipping readers with critical technical tips and tricks to use popular presentation programs like PowerPoint or Keynote effectively. The book details numerous remedial measures for qualitative improvement of average medical presentations. It has three sections: first covers the general aspects of preparing a presentation; the second provides practical details and refinements of preparing a medical presentation; the last section deals with niceties of podium and webinar presentations. The chapters cover many serious mistakes and remedial measures to improve average medical presentations, such as a description of purposeful use of colors in a slide, a brief discourse on technicalities of appropriate clinical image formats for projection ensues; the use of drawing and photo-editing programs to inject excellence in the contents of a medical presentation to help it stand out in the crowd, details on the importance of lexical correctness- typography, line spacing and alignment to enhance the impact of the presented text and many more. Several short videos support and actively promote the viewpoints discussed in the text. This book elaborates on the exquisite art of creating remarkable medical presentations for a specialized audience. This book is a must-have for all healthcare professionals of all specialties and grades who make podium presentations in a medical conference webinar or submit posters for display.
Philosophy of inception: Why a book on presentations -- Optics of slide design & projection -- Rational use of colour in presentations -- Digital Imaging and formats -- Supportive Apps -- Background -- The text slides -- Data presentation: Use of tables and graphics -- Use of photographs in medical presentations -- Showing X-ray, MRI, CT, and Ultrasound images in presentations -- Use of illustrations in medical presentations -- Adding Videos in presentations -- Posters for medical & scientific meetings -- An approach to podium and webinar presentations -- Audiovisual planning for a large medical conference.
Keywords: Premedical education; Medical education; Communication in medicine; Premedical Education; Medical Education; Health Communication; Communication; Medicine; Microsoft PowerPoint (Computer file)